2015
DOI: 10.4314/sajas.v45i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Correlations of Backfat Thickness with Meatiness Traits, Intramuscular Fat, <i>Longissimus</i> Muscle Cholesterol and Fatty Acid Composition in Pigs

Abstract: The aim of the present study was to determine the phenotypic correlations of backfat thickness with meatiness traits and intramuscular fat, cholesterol and fatty acid composition in the longissimus muscle of pigs. For this study, 60 barrows and 60 gilts (Pietrain × Duroc boars and Polish Large White crossbred sows) were slaughtered at 100 kg bodyweight. Lean meat percentage (LMP), loin muscle area (LMA), backfat thickness measured at five locations and average backfat thickness (ABF), and intramuscular fat (IM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
3
13
2
Order By: Relevance
“…In the present study, differences in relative amounts of fatty acids were found between pig muscles and this is in agreement with the fi ndings of Realini et al [20]. The proportions of fatty acids in the pork from Lithuanian White pigs were similar to those reported for the hybrid pigs by Jacyno et al [19], but different to those reported by Hanczakowska et al [28]. Despite the fact that goose is a minor component of poultry production, there is also suffi cient interest in goose meat for nutrition diversifi cation.…”
Section: Fatty Acid Profi Lessupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, differences in relative amounts of fatty acids were found between pig muscles and this is in agreement with the fi ndings of Realini et al [20]. The proportions of fatty acids in the pork from Lithuanian White pigs were similar to those reported for the hybrid pigs by Jacyno et al [19], but different to those reported by Hanczakowska et al [28]. Despite the fact that goose is a minor component of poultry production, there is also suffi cient interest in goose meat for nutrition diversifi cation.…”
Section: Fatty Acid Profi Lessupporting
confidence: 93%
“…The present study indicated high variations of fat both between the studied animal species and the individuals of the analysed species and between different muscles. These results are in agreement with the report of Hocquette et al [16] and Jacyno et al [19] who showed a high variability of intramuscular fat in the longissimus muscle of Polish hybrid pigs and Realini et al [20] who found large differences between pig muscles. Low intramuscular fat content of red deer found in the present study is in agreement with the review of Daszkiewicz and Mesinger [21].…”
Section: Intramuscular Fat Contentsupporting
confidence: 93%
“…The above relationships are confirmed by the coefficients of correlation between IMF content vs. total SFAs, MUFAs and the P/S ratio in meat from livestock. [35][36][37] In a study by Strazdina et al [16] , IMF extracted from the LL muscle of red deer, compared with roe deer, had higher concentrations of C18:2 and MUFAs: C14:1, C16:1, C24:1, . The IMF of roe deer contained higher amounts of C18:1 and PUFAs: C20:3, C20:4, C20:5, .…”
Section: Resultsmentioning
confidence: 99%
“…For a long time, the major objective of pig breeding programs was to increase the carcass meat percentage for higher feed efficiency since approximately fourfold as much energy is required to grow 1 kg of fat tissue compared with 1 kg of lean tissue (18). BFT and CFP are the most important fatness traits considered in pig breeding improvement and are negatively correlated to lean percentage (50,51). Fat-type pig breeds, including European breeds, such as Mangalica and the Iberian pigs (52), and Chinese breeds, such as Erhualian, Meishan, and Bama pigs (53), produce high-quality meat with desirable palatability attributes, but they have poor Relative mitochondria copy number analysis of inguinal sub and perirenal fat showed no difference between the two genotypes (n = 4 per group).…”
Section: Discussionmentioning
confidence: 99%